The effect of Phase Composition on the Photocatalytic Activity of Cu₂O/CuO/Cu Composites for Methylene Blue Photodegradation - Rizqi Maulana, Mokhamad Ali; Aisyaturridha; Bimo TriGoutomo; Amir Mahmud (Pusat Inovasi Sains, 2025)
This study investigates the influence of phase composition on Cu₂O/CuO/Cu composites for the degradation methylene blue (MB) under visible light irradiation. Two types of composites, Cu₂O-rich and Cu₂O-poor, were successfully synthesized through electrodeposition method. The results showed that the Cu₂O-rich composite exhibited photocatalytic activity, as indicated by a maximum photocurrent of 13 mA/cm² and the highest optimized MB photodegradation efficiency. This enhanced performance is due to the high Cu₂O phase content, which generates a higher photocurrent density, thereby accelerating the redox reaction in the MB degradation.